Post-heating response of concrete-filled steel tubular columns under sustained loads. (October 2019) - Ibañez, C.; Bisby, L.; Rush, D.; Romero, M.L.; Hospitaler, A.
Abstract: Concrete-filled steel tubular (CFST) columns can generally be expected to better resist elevated temperatures as compared to unfilled steel hollow sections, whose evaluation after a fire is limited by the resulting deformation. A better understanding of the behaviour of CFST columns after a fire, which is dominated by the maximum temperature achieved by the concrete infill and plasticity of the steel, is required to properly estimate their residual strength and deformation and to adopt a reasonable strategy with minimum post-fire repair. In this paper, a fibre beam model for the simulation of the post-heating response of concrete-filled steel tubular (CFST) columns is presented. First, the model is validated against experimental results and subsequently it is employed to analyse the post-heating response of circular CFST columns under sustained loads. In reality, during a fire, the columns support load even during the cooling phase of a fire, so it is important to consider this loading condition when predicting the post-fire behaviour. The analysis presented in this paper comprises three stages: heating, cooling and post-fire (under sustained load) conditions. The model considers realistic features typical of the fire response of CFST columns, such as the existence of a gap conductance at the steel-concrete interface and the sliding and separation of the steel tube and the concrete. Based on the model, the response of CFST columns after heating is investigated via parametric analysis.